Alveolar macrophage activity and the pulmonary complications of haematopoietic stem cell transplantation. Issue 12 (1st December 2001) - Whittle, A T; Davis, M; Shovlin, C L; Ganly, P S; Haslett, C; Greening, A P
Abstract : BACKGROUND: The success of haematopoietic (bone marrow or peripheral blood) stem cell transplantation (SCT) is compromised by pulmonary complications. We hypothesised that a proinflammatory alveolar microenvironment, reflected in alveolar macrophage (AM) cytokine production, would predispose to such complications. METHODS: AM were isolated from adult SCT recipients by bronchoalveolar lavage before SCT (n=32) and during post-transplant pancytopenia (n=23). Concentrations of tumour necrosis factor (TNF)α, granulocyte-macrophage colony stimulating factor (GM-CSF), interleukin (IL)-1β, IL-6, and IL-8 in 24 hour AM culture medium were measured by enzyme linked immunosorbent assay and compared with both the occurrence of post-SCT lung disease and with subjects' previous respiratory histories. RESULTS: Eleven subjects developed lung disease within 6 months of SCT. These subjects had higher median pre-transplant AM TNFα (8 (IQR 1–8) v 2 (1–5) ng/10 6 AM, p=0.01, median difference (D) = 3, 95% CI 0.1 to 7), GM-CSF (5 (0.7–8) v 0.2 (0.1–0.8), p=0.006, D = 4, 95% CI 0.5 to 7), and IL-6 (0.5 (0.1–1) v 0.1 (0.02–0.3), p=0.049, D = 0.3, 95% CI 0.0002 to 1) production than remaining subjects; IL-1β and IL-8 did not differ. During pancytopenia high AM GM-CSF production again predicted later lung disease (1 (0.7–9) v 0.1 (0.06–0.3), p=0.01, D = 1, 95% CI 0.1 to 6). A history of recent chest disease was associated with high AM TNFα and GM-CSF production and with post-SCT lung disease. Pre-SCT lung function was unrelated to post-SCT lung disease. CONCLUSIONS: Recent respiratory disease and persistent proinflammatory AM behaviour detectable before transplantation are associated with lung disease following SCT. These associations may prove useful in pre-transplant risk assessment.